BOOKS RECENTLY PUBLISHED. (Notes, 2009)
The article lists books related to music including "Singing Through the Church Year: A Children's Choir Resource Book," by Tamara Makdad Albrecht, "Imposing Harmony: Music and Society in Colonial Cuzco," by Geoffrey Baker and "Technology Integration in the Elementary Music Classroom," by Amy M. Burns.